O letreiro de Pilatos: um estudo exegético de Jo 19,19-22 - Grenzer, Francisca Antonia de Farias (2020)
According to the testimony of the four New Testament Gospels, there was an “epigraph” (Mk 15:26; Lk 23:38) or a “placard” (Jn 19:19.20) “above the head of Jesus” crucified (Mt 27:37). Historically, it is the first “writing” or “epigraphed” text about the Nazarene (Mt 27:37; Mk 15:26; Jn 19:19.20.21.222x). Moreover, according to the Fourth Gospel, the text “written by Pilate in Hebrew, Latin, and Greek” (Jn 19:20), and “read by many Jews” (Jn 19:20), soon provoked a controversy among the religious leaders of the Jews and the Roman governor (Jn 19:21-22). The intention of this Dissertation is to investigate, in a linguistic-literary and historical-theological way, what, according to Gospel of John, was written in that placard, knowing that the Christian tradition, in its iconographic representations of the crucified, welcomes the Johannine text